THE UTILISATION OF ARTIFICIAL INTELLIGENCE, INTERNET OF THINGS, AND VIRTUAL/AUGMENTED REALITY IN ENHANCING THE EFFECTIVENESSAND EFFICIENCY OF LEARNING: A LITERATURE REVIEW - Risqah Amaliah Kasman; Al-Amin (Indonesian Journal of Education (INJOE), 2025)
The rapid development of digital technology has brought fundamental changes to the world of education, particularly through the use of Artificial Intelligence (AI), Internet of Things (IoT), and Virtual and Augmented Reality (VR/AR). This literature study aims to examine the role and impact of these three technologies in improving the effectiveness and efficiency of learning. The findings reveal that AI enables personalised learning materials, automated assessment, and real-time analysis of students' achievements, making the learning process more responsive and adaptive to individual needs. IoT creates an integrated learning environment, enabling monitoring of learning conditions, optimisation of resources, and improved access and inclusivity. Meanwhile, VR/AR provides immersive learning experiences that strengthen the understanding of abstract concepts, increase learning motivation, and support the development of students' practical skills without real risk. Despite their many potential benefits, the adoption of these three technologies also faces challenges related to infrastructure, digital literacy, data security, and human resource readiness. The integration of AI, IoT, and VR/AR has proven to be a key driver of educational innovation, but a comprehensive implementation strategy is necessary to maximise their impact on improving the quality of education in the digital age.